Creation of a Mudra batik business in the Wirausaha Merdeka Program of Universitas Muhammadiyah Surakarta - Mustofa, Muhamad; Setyawan, Anton Agus (Journal of Community Service and Empowerment, 2023)
The implementation of the Wirausaha Merdeka program was motivated by the rising unemployment rate in Indonesia, which prompted the government to make a breakthrough by encouraging student interest and enthusiasm in entrepreneurship, instilling a mindset and fundamental competencies in the field of entrepreneurship, encouraging more entrepreneurial experience among students, boosting student employability and assisting in the development of university graduates' capacity and quality. The method used is a combination of learning by doing, training, and mental empowerment of student business. The activities were carried out in an engaging, participatory manner, with Field Supervisors (DPL) and one Mentor from UMKM partners accompanying each group of five students. In conclusion, the Wirausaha Merdeka program can effectively increase motivation, increase competence and foster entrepreneurial interest. There were significant improvements both before and after the Wirausaha Merdeka program was implemented.